E-Learning Sebagai Evolusi Proses Pembelajaran di Era Masyarakat Informasi - Putu Kussa Laksana Utama (Jurnal Penjaminan Mutu, 2017)
Education is a important thing in a human civilization history. The progress of a civilization is mostly determined by education as a main factor. Throughout the history of human civilization, there were so many learning methods has been invented such as discussion method, discourse method, group teaching, and technology-supported learning method. The fast development of Information and Communication Technology (ICT) in the era of information society has facilitated all of knowledge seekersnowdays to learn something better and better.E-Learning as a implementation of ICT in education domain takes the role as a education media which provide education content so that the students are able to access it times infinity.